The Arabidopsis Protein CGL20 Is Required for Plastid 50S Ribosome Biogenesis - Reiter, Bennet (Plant Physiol, 2020)
Biogenesis of plastid ribosomes is facilitated by auxiliary factors that process and modify ribosomal RNAs (rRNAs) or are involved in ribosome assembly. In comparison with their bacterial and mitochondrial counterparts, the biogenesis of plastid ribosomes is less well understood, and few auxiliary factors have been described so far. In this study, we report the functional characterization of CONSERVED ONLY IN THE GREEN LINEAGE20 (CGL20) in Arabidopsis (Arabidopsis thaliana; AtCGL20), which is a Pro-rich, ∼10-kD protein that is targeted to mitochondria and chloroplasts. In Arabidopsis, CGL20 is encoded by segmentally duplicated genes of high sequence similarity (AtCGL20A and AtCGL20B). Inactivation of these genes in the atcgl20ab mutant led to a visible virescent phenotype and growth arrest at low temperature. The chloroplast proteome, pigment composition, and photosynthetic performance were significantly affected in atcgl20ab mutants. Loss of AtCGL20 impaired plastid translation, perturbing the formation of a hidden break in the 23S rRNA and causing abnormal accumulation of 50S ribosomal subunits in the high-molecular-mass fraction of chloroplast stromal extracts. Moreover, AtCGL20A-eGFP fusion proteins comigrated with 50S ribosomal subunits in Suc density gradients, even after RNase treatment of stromal extracts. Therefore, we propose that AtCGL20 participates in the late stages of the biogenesis of 50S ribosomal subunits in plastids, a role that presumably evolved in the green lineage as a consequence of structural divergence of plastid ribosomes.